Completeness of Lexicographic Products of GO-Spaces - Kemoto, Nobuyuki (Topology Proceedings, 2020)
Variations of Dedekind completeness of lexicographic products of GO-spaces are studied. As a corollary, we see that whenever γ is limit and all GO-spaces X_α ’s have minimal elements but have no maximal elements, connectedness of a lexicographic product _α < γ X_α implies non-connectedness of all X_α ’s.